Sistem pengendalian simetris: bercermin pada subak, mematut sistem pengendalian intern pemerintahan - Sylvia Sylvia; Rohmawati Kusumaningtias; Alia Ariesanti (Jurnal Akuntansi Aktual, 2020)
Abstract: This paper aims to interpret the values carried out in subak to be reflected in the strengthening of the internal control system in local government. Weak internal controls result in corruption being an unresolved problem in local government. Corruption shows the denial of humans to submit to the creator while still being obliged to maintain harmony with fellow human beings and with nature. Library research was conducted on the Subak system run by the Hindu-Balinese community and the phenomenon of corruption that occurred in this country. The results show that the symmetrical control system carried out in the subak is able to harmonize faith, the necessities of life, and the preservation of nature. Tri Hita Kirana which is the foundation of the subak governance  is carried out by linking organizational goals to harmonizing relationships with God, humans, and nature. This symmetrical internal control system reflects religious values, justice, and togetherness which are expected to strengthen the internal control system of the local government.Abstrak: Makalah ini bertujuan memaknai nilai-nilai yang dijalankan di subak untuk direfleksikan pada penguatan sistem pengendalian intern di pemerintahan daerah. Pengendalian intern yang lemah mengakibatkan korupsi menjadi masalah yang belum  terselesaikan di pemerintahan daerah. Korupsi menunjukkan pengingkaran manusia untuk tunduk pada Sang Maha Pencipta sembari tetap berkewajiban menjaga keharmonisan  dengan  sesama manusia  dan  alam. Riset  kepustakaan  dilakukan atas sistem subak yang dijalankan oleh masyarakat Hindu-Bali dan fenomena korupsi yang terjadi di tanah air. Hasilnya menunjukkan bahwa sistem pengendalian simetris yang  dijalankan di subak mampu menyelaraskan antara iman, kebutuhan hidup, dan kelestarian alam. Tri Hita Kirana yang menjadi landasan tata kelola subak dilakukan dengan cara menautkan tujuan organisasi pada harmonisasi hubungan dengan Tuhan, manusia, dan alam. Sistem pengendalian intern simetris ini merefleksikan nilai religius, keadilan, dan kebersamaan yang diharapkan dapat menguatkan sistem pengendalian intern pemerintah daerah.